2020
DOI: 10.3390/molecules25225246
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polyheterocyclic Dimers Containing Restricted and Constrained Peptidomimetics via IMCR-Based Domino/Double CuAAC Click Strategy

Abstract: A novel strategy via the triple process (multicomponent reactions (MCR)-domino)/tandem was developed for the synthesis of restricted and constrained bis-1,2,3-triazole-linked pyrrolo[3,4-b]pyridine peptidomimetics dimers in overall yields of 20–55%. This strategy allows the construction of six heterocycles in two stages of the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…We synthesized a series of novel alkynes 9 a-i (Figure 1), which could serve as efficient building blocks to generate structural diversity. [11] Following our main research line focused on the design and development of efficient IMCR-based strategies to synthesize novel CCP, in one-pot, [35][36][37][38] or two steps [43][44][45] we Recently, we reported the one-pot DOS of CCP via IMCR/post-transformation strategy. [39] Herein, we increased the complexity of CCP including heterocyclic bioisosteres of the amide bond such as 1,2,3-triazoles and 1,5-DSÀ T.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We synthesized a series of novel alkynes 9 a-i (Figure 1), which could serve as efficient building blocks to generate structural diversity. [11] Following our main research line focused on the design and development of efficient IMCR-based strategies to synthesize novel CCP, in one-pot, [35][36][37][38] or two steps [43][44][45] we Recently, we reported the one-pot DOS of CCP via IMCR/post-transformation strategy. [39] Herein, we increased the complexity of CCP including heterocyclic bioisosteres of the amide bond such as 1,2,3-triazoles and 1,5-DSÀ T.…”
Section: Resultsmentioning
confidence: 99%
“…According to our research line, we are interested in the development of novel strategies to access structural peptidomimetics coupling IMCRs with other efficient one-pot processes, [35][36][37][38] and their application in DOS. [39] Herein we describe a new DOS strategy to synthesize anchored analogues of 2,5-DKP fused to 1,2,3-triazole, with scaffold diversity incorporating a tetrazole ring in their structure (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…Following our main research line focused on the design and development of efficient IMCR-based strategies to synthesize compounds of interest [9][10][11][12][13][14][15], in 2017, our research group reported the first ultrasound-assisted Ugi-azide reaction under solvent-free conditions using aromatic aldehydes and amines (Scheme 1) [16].…”
Section: Resultsmentioning
confidence: 99%